Solution:
The standard equation of a hyperbola is expressed as
![\begin{gathered} \frac{(x-h)^2}{a^2}-\frac{(y-k)^2}{b^2}=1\text{ \lparen parallel to the x-axis\rparen} \\ \frac{(y-k)^2}{a^2}-\frac{(x-h)^2}{b^2}=1\text{ \lparen parallel to the y-axis\rparen} \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%20%5Cfrac%7B%28x-h%29%5E2%7D%7Ba%5E2%7D-%5Cfrac%7B%28y-k%29%5E2%7D%7Bb%5E2%7D%3D1%5Ctext%7B%20%5Clparen%20parallel%20to%20the%20x-axis%5Crparen%7D%20%5C%5C%20%5Cfrac%7B%28y-k%29%5E2%7D%7Ba%5E2%7D-%5Cfrac%7B%28x-h%29%5E2%7D%7Bb%5E2%7D%3D1%5Ctext%7B%20%5Clparen%20parallel%20to%20the%20y-axis%5Crparen%7D%20%5Cend%7Bgathered%7D)
Given that the hyperbola has its foci at (0,-15) and (0, 15), this implies that the hyperbola is parallel to the y-axis.
Thus, the equation will be expressed in the form:
![\frac{(y-k)^2}{a^2}-\frac{(x-h)^2}{b^2}=1\text{ ----equation 1}](https://tex.z-dn.net/?f=%5Cfrac%7B%28y-k%29%5E2%7D%7Ba%5E2%7D-%5Cfrac%7B%28x-h%29%5E2%7D%7Bb%5E2%7D%3D1%5Ctext%7B%20----equation%201%7D)
The asymptote of n hyperbola is expressed as
![y=\pm\frac{a}{b}(x-h)+k](https://tex.z-dn.net/?f=y%3D%5Cpm%5Cfrac%7Ba%7D%7Bb%7D%28x-h%29%2Bk)
Given that the asymptotes are
![y=\frac{3}{4}x\text{ and y=-}\frac{3}{4}x](https://tex.z-dn.net/?f=y%3D%5Cfrac%7B3%7D%7B4%7Dx%5Ctext%7B%20and%20y%3D-%7D%5Cfrac%7B3%7D%7B4%7Dx)
This implies that
![a=3,\text{ and b=4}](https://tex.z-dn.net/?f=a%3D3%2C%5Ctext%7B%20and%20b%3D4%7D)
To evaluate the value of h and k,
The main point which will immediately make it clear is that you have to plug in 2 for x so that you can find the linit. So, using this simple method you will get the <span>-1/4 answer. Hope you will agree with me and find this useful! Regards.</span>
4x+2y=10 Equation 1
x-y=13 Equation 2
Solving by substitution method.
Isolate x from equation 2.
x=y+13
Substitute value of x in equation 1
4(y+13)+2y=10
4y+52+2y=10
6y+52=10
6y=-42
y=-7
Now substitute value of y in x=y+13
x=-7+13
x=6
Answer: (6,-7)
Step-by-step explanation:
so first you combine like terms , 3x-x-4=4 turns into 4x-4=4 then u add 4 to both sides [inverse operations]
4x-4=4
+4 +4
--------------
4x= 8
----------
4. 4
×=2
then u use inverse operations. agian and divide 4 into 8 and you get 2 !! x = 2
Answer:
triangle
Step-by-step explanation: